Trigonella foenum-graecum seeds in treatment of metabolic syndrome - Kania-Dobrowolska Małgorzata; Baraniak Justyna (Herba Polonica, 2020)
Fenugreek has a long tradition of use as a medicine and also has been commonly used as food in many countries. This plant is well known, especially in Asia. In Europe, fenugreek seeds are regarded as a traditional herbal medicine consumed in case of loss of appetite and in confirmed skin inflammations. Trigonella foenum-graecum seeds contain wide spectrum of different biologically active constituents which affect the properties of preparations produced from this plant. Numerous preclinical studies confirm the use of fenu-greek as a hypolipidemic and lowering blood glucose level drug. Unfortunately, there are not many clinical studies on fenugreek seeds in this area. Published studies often significantly differ in the amount and type of fenugreek seed preparation used. However, results of available scientific research are promising and suggest the possibility of using fenugreek seeds in metabolic syndrome therapy. Undoubtedly, further research is required to confirm such properties of Trigonella foenum-graecum.